On Optimal Scarcity Prices - Gregor Zöttl (Verein für Socialpolitik, 2010)
This article contributes to the debate of missing money (e.g. Joskow(2007)) which has seriously questioned the desirability of caps on scarcity prices in markets with fluctuating demand by emphasizing their potentially negative impact on firms investment decisions in the long run. A prominent example are recently liberalized electricity markets, where competition authorities have imposed caps in order to mitigate the exercise of market power at the spot markets. In order to shed light on the still incompletely explored impact of such caps in the long run we analyze investment of strategic firms in base
Keywords: D43; L51; L94; 330; load and peak